Décalcification resistance of various alkali-activated materials. Issue 1 (November 2021) - Hruby, P; Bilek, V; Topolar, L; Kalina, L; Marko, M; Soukal, F; Dvorak, R; Hercik, T
Abstract: The resistance of alkali-activated materials (AAMs) to degradation processes, particularly the decalcification, was studied in this paper. The ground granulated blast furnace slag was alkali-activated using various activators with the same activator dosage 6% Na2 O by slag weight (sodium hydroxide, sodium waterglass and sodium carbonate) and subjected to testing of decalcification resistance (immersion in 6M NH4 NO3 ) for 84 days. The reference samples were stored in water. The progress of degradation was studied using the phenolphthalein technique, mechanical properties testing (compressive and flexural strength), and dilatometry analysis or weight measurements. The results obtained were compared to the CEM III/A 32.5R. The significant loss of mass along with the deterioration of mechanical properties were observed for all binder types, still some of the AAMs showed better durability than the cementitious one.